2022
DOI: 10.1186/s12877-022-02925-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum creatinine/cystatin C ratio as a screening tool for sarcopenia and prognostic indicator for patients with esophageal cancer

Abstract: Background & aims Sarcopenia is associated with poor clinical outcomes of patients who underwent esophagectomy. The current diagnostic criteria for sarcopenia are complex and laborious. We aimed to employ the simple and economic indicator sarcopenia index (SI = creatinine/cystatin C ×100) to screen for sarcopenia and to evaluate its prognostic value in patients with esophageal cancer (EC). Methods Older participants in the National health and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 43 publications
4
44
2
1
Order By: Relevance
“…The study showed that Cr/CysC ratio (OR = 4.722, 95% CI: 2.312-33.871, p = 0.002) remained an independent predictor of sarcopenia in GIST patients after adjustment of BMI, tumour size, risk classification and Cr by multivariate logistic regression analysis, which is consistent with previous findings in gastric cancer patients (18). In addition, a retrospective study by Zheng et al found that the ratio of Cr/CysC had a good diagnostic effect on sarcopenia in both men (AUC = 0.732) and women (AUC = 0.754) with oesophageal cancer (17). Similar results were obtained in the present study, the serum Cr/CysC ratio was a useful predictor of sarcopenia compared with other biomarkers (e.g., serum Cr, CysC), and subgroup analysis performed according to gender found that the serum Cr/CysC ratio could also predict sarcopenia in GIST patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study showed that Cr/CysC ratio (OR = 4.722, 95% CI: 2.312-33.871, p = 0.002) remained an independent predictor of sarcopenia in GIST patients after adjustment of BMI, tumour size, risk classification and Cr by multivariate logistic regression analysis, which is consistent with previous findings in gastric cancer patients (18). In addition, a retrospective study by Zheng et al found that the ratio of Cr/CysC had a good diagnostic effect on sarcopenia in both men (AUC = 0.732) and women (AUC = 0.754) with oesophageal cancer (17). Similar results were obtained in the present study, the serum Cr/CysC ratio was a useful predictor of sarcopenia compared with other biomarkers (e.g., serum Cr, CysC), and subgroup analysis performed according to gender found that the serum Cr/CysC ratio could also predict sarcopenia in GIST patients.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these characteristics, the calculation of the Cr/CysC ratio can be used to assess skeletal muscle metabolism and further screen patients for sarcopenia. Since its introduction, the serum Cr/CysC ratio has been widely evaluated as a valid, low-cost, and reproducible biomarker in a variety of diseases, such as gastric cancer (18), oesophagal cancer (17), idiopathic pulmonary fibrosis (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that pectoralis muscle area, determined by CT scan at the time of ICU admission, was associated with 6-month and hospital survival, as well as ICU-free days, despite not being a good predictor of regaining an independent lifestyle after discharge. Zheng et al [ 38 ] demonstrated that lower CCR could be used to identify sarcopenia in patients with esophageal cancer and was associated with shorter overall survival. Further, they found the all-cause mortality risk gradually decreased with increased CCR.…”
Section: Discussionmentioning
confidence: 99%
“…As we all know, serum creatinine and cystatin C are both biomarkers for glomerular filtration and renal function. Recently, a surrogate marker for sarcopenia called sarcopenia index (SI) has deen developed, which is defined as serum creatinine (mg/dL)/cystatin C (mg/L) × 100 and can be used to evaluate the skeletal muscle mass (Kashani et al, 2017;Barreto et al, 2019;Ren et al, 2022;Zheng et al, 2022). As we know, serum creatinine is the derivative of the skeletal muscle protein and the production of serum creatinine changes with skeletal muscle mass.…”
Section: Introductionmentioning
confidence: 99%